A search for the sulphur hexafluoride cation with intense, few cycle laser pulses - Dota, Krithika; Dharmadhikari, Aditya K.; Dharmadhikari, Jayashree A.; Patra, Kaustuv; Tiwari, Ashwani K.; Mathur, Deepak (The Journal of chemical physics, 2013)
It is well established that upon ionization of sulphur hexafluoride, the SF6+ ion is never observed in mass spectra. Recent work with ultrashort intense laser pulses has offered indications that when strong optical field are used, the resulting “bond hardening” can induce changes in the potential energy surfaces of molecular cations such that molecular ions that are normally unstable may, indeed, become metastable enough to enable their detection by mass spectrometry. Do intense, ultrashort laser pulses permit formation of SF6+? We have utilized intense pulses of 5 fs, 11 fs, and 22 fs to explore this possibility. Our results are negative: no evidence is discovered for SF6+. However, multiply charged sulphur and fluorine ions from highly charged SF6q+ ions are observed that enable us to resolve the controversy regarding the kinetic energy release accompanying formation of F+ fragment ions. Quantum chemical computations of field-distorted potential energy curves of SF6 and its molecular ion enable us to rationalize our non-observation of SF6+. Our findings have implications for high harmonic generation from SF6 in the few-cycle regime.